A novel rice fragile culm 24 mutant encodes a UDP-glucose epimerase that affects cell wall properties and photosynthesis. (17th February 2020) - Zhang, Ran; Hu, Huizhen; Wang, Youmei; Hu, Zhen; Ren, Shuangfeng; Li, Jiaying; He, Boyang; Wang, Yanting; Xia, Tao; Chen, Peng; Xie, Guosheng; Peng, Liangcai
Abstract: UDP-glucose epimerases (UGEs) are essential enzymes for catalysing the conversion of UDP-glucose (UDP-Glc) into UDP-galactose (UDP-Gal). Although UDP-Gal has been well studied as the substrate for the biosynthesis of carbohydrates, glycolipids, and glycoproteins, much remains unknown about the biological function of UGEs in plants. In this study, we selected a novel rice fragile culm 24 ( Osfc24 ) mutant and identified it as a nonsense mutation of the FC24/OsUGE2 gene. The Osfc24 mutant shows a brittleness phenotype with significantly altered cell wall composition and disrupted orientation of the cellulose microfibrils. We found significantly reduced accumulation of arabinogalactan proteins in the cell walls of the mutant, which may consequently affect plant growth and cell wall deposition, and be responsible for the altered cellulose microfibril orientation. The mutant exhibits dwarfism and paler leaves with significantly decreased contents of galactolipids and chlorophyll, resulting in defects in plant photosynthesis. Based on our results, we propose a model for how OsUGE2 participates in two distinct metabolic pathways to co-modulate cellulose biosynthesis and cell wall assembly by dynamically providing UDP-Gal and UDP-Glc substrates. Abstract : A novel rice fragile culm mutant ( Osfc24 ) possesses a nonsense mutation of OsUGE2 encoding a UDP-Glc epimerase, which participates in metabolic pathways that affect both cell wall properties and photosynthesis.